2010
DOI: 10.1021/cg1005049
|View full text |Cite
|
Sign up to set email alerts
|

Doping Uric Acid Crystals. 1. Uric Acid Dihydrate

Abstract: The crystallization of uric acid dihydrate (UAD) from model supersaturated aqueous solutions containing 21 different molecular dye probes and 11 inorganic salts was investigated. UAD crystals grown at room temperature were found to include low concentrations (0.01-0.42%) of cationic and neutral dyes but not anionic dyes. From dilute dye solutions, a preference for inclusion in either {011} or {102} growth sectors was exhibited for some dyes while others showed little specificity. At higher dye concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…The first studies on uric acid crystallization in the presence of colorants began in the 1930s, when Gaubert examined crystals grown in the presence of various synthetic dyes. Kleeberg added to this body of work with additional dye studies in the 1970s. , More recent work in our lab has shown that low concentrations of a wide variety of neutral and cationic dyes can be included in UA and UAD , often with high specificity. , When a cationic dye is included, charge-balance can be achieved by the parallel inclusion of a urate ion. For example, methylene blue (and several other dyes) is selectively included in {001} and {201} growth sectors of UA .…”
Section: Resultsmentioning
confidence: 99%
“…The first studies on uric acid crystallization in the presence of colorants began in the 1930s, when Gaubert examined crystals grown in the presence of various synthetic dyes. Kleeberg added to this body of work with additional dye studies in the 1970s. , More recent work in our lab has shown that low concentrations of a wide variety of neutral and cationic dyes can be included in UA and UAD , often with high specificity. , When a cationic dye is included, charge-balance can be achieved by the parallel inclusion of a urate ion. For example, methylene blue (and several other dyes) is selectively included in {001} and {201} growth sectors of UA .…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of available X-ray and Raman data, it seemed more likely that the emergent UA crystal pairs were due to related defects introduced by the presence of 24-DAP in the growth solution. We know from previous work that when UAD is grown from solutions containing assorted dye additives, low concentrations of the dye in solution (<0.1%) can become trapped in the resultant crystal . Similarly, direct-injection mass spectrometry confirmed that trace amounts of 24-DAP were present in the UAD prisms (Figure S5).…”
mentioning
confidence: 95%
“…A key point of this discussion is the birefringence nature of the compound associated with the metallic-like structural color of these beetles [30,31,32,33,34,35], which should be deposited within the chitin structure. There are many reports of doping or functionalized uric acid [48,49,50,51,52], but not all of them present a birefringence [48]. The chemical extraction of the PCOC sample was attempted by using the method suggested by Caveney [38].…”
Section: Resultsmentioning
confidence: 99%